2010
DOI: 10.3748/wjg.v16.i2.167
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind trial on perioperative administration of probiotics in colorectal cancer patients

Abstract: La1, but not BB536, adheres to the colonic mucosa, and affects intestinal microbiota by reducing the concentration of pathogens and modulates local immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
113
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(120 citation statements)
references
References 37 publications
0
113
0
7
Order By: Relevance
“…Administration of probiotics in these patients aims a competitive action against bacteria responsible for postoperative inflammation (9). Thus, it has been suggested that probiotics play an essential role in the stability of the microbiological environment (10,11).…”
Section: Original Articlementioning
confidence: 99%
“…Administration of probiotics in these patients aims a competitive action against bacteria responsible for postoperative inflammation (9). Thus, it has been suggested that probiotics play an essential role in the stability of the microbiological environment (10,11).…”
Section: Original Articlementioning
confidence: 99%
“…Although the results of systematic and wellcontrolled clinical studies in CRC prevention are not yet available, published reports suggest cautious optimism. [58][59][60] Although our study design does not address causality, it is plausible that curcumin contributes to chemoprevention via expansion of the native Lactobacilli in the context of overall increase of colonic microbiome richness. Similar effects may be ascribed to increased Bifidobacteria, which have also been shown to reduce aberrant crypt foci in mice receiving dimethylhyrazine.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus johnsonii and Lactobacillus casei suppress CRC tumor growth in patients and modulate the intestinal immune response. 110,111 Antibiotics have long been used to eradicate H pylori in the upper GI tract, and treatment is associated with a significant reduction in gastric Another growing area of interest is in modulating the gut microbiota to prevent toxicity associated with the chemotherapy and radiation used to treat cancer. A recent study identified the role of bacterial beta-glucuronidase in mediating GI toxicity of a common drug used for colon cancer CPT-11.…”
Section: Gut Microbiota In Malignancymentioning
confidence: 99%